Effect of streptomycin on the growth of Solanum lycopersium L. - Aquino, Odilio Keefe Miguel P. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
The use of antibiotics and their impact on plants calls for further research to be required. In the agricultural sector, research concerning plant growth and antibiotics is important in order to determine whether they pose a significant effect on plant growth. As antibiotics enter the soil through wastewater irrigation and from animal manure, residual amounts of antibiotics can enter the plant system and impact plant growth. A pot experiment employing a completely randomized design was conducted to determine how the presence of antibiotics, specifically streptomycin, in soil affects the growth of Solanum lycopersicum L. Six plants were randomly assigned to each treatment of antibiotic concentration (0 μg/L, 1 μg/L, 5 μg/L, 10 μg/L, 1 mg/L, and 10 mg/L). The application of antibiotics was done twice per week. The root weight, root length, plant height, and leaf area were measured and factors such as the RGR, SLA, SRL, RMF, LMF, and SMF were calculated to further quantify the difference in growth among the treatment groups. Results showed that the presence of streptomycin does not affect the growth of Solanum lycopersicum L. with regards to the six measured factors in any way. Even at high concentrations, the presence of streptomycin did not pose a significant effect on the growth of Solanum lycopersicum L. As such, with regards to plant-antibiotic specificity, streptomycin does not interact with the growth of Solanum lycopersicum L.